Periconceptional folic acid supplement use among women of reproductive age and its determinants in central rural Germany: Results from a cross sectional study. Issue 14 (22nd May 2020) - Wegner, Clara; Kancherla, Vijaya; Lux, Anke; Köhn, Andrea; Bretschneider, Dirk; Freese, Kristina; Heiduk, Mathias; Redlich, Anke; Schleef, Daniela; Jorch, Gerhard; Rissmann, Anke
Abstract: Background: Prevalence of neural tube defects (NTD) has not decreased in Germany despite longstanding recommendations for folic acid supplementation. To examine the prevalence of periconceptional folic acid supplement use and associated factors among German women of reproductive age. Methods: Cross‐sectional survey was conducted in hospital‐based maternity units in rural Germany. A sample of 1, 004 women of reproductive age, either pregnant or in their early postpartum period, took interviewer/self‐administered paper‐based survey questionnaire. Prevalence of periconceptional folic acid supplement use was assessed, where periconception was defined as 1 month prior to and 3 months post‐conception. Prevalence odds ratios (POR) and 95% confidence intervals (CI) using crude and adjusted logistic regression analysis were estimated to examine determinants of folic acid supplement use. Results: Prevalence of folic acid supplement use was 41.5% (95% CI: 37.7%, 45.7%). Multivariable analysis showed lack of educational qualifications, unplanned pregnancy, later diagnosis of pregnancy, increased parity, and not having an awareness of importance of folic acid for optimal pregnancy outcomes were associated with not taking periconceptional folic acid supplements. Books, doctors, friends, media, were sources of information. Conclusion: Periconceptional folic acid is sub‐optimal in rural Germany and thus failing to prevent NTDs. Targeted promotion of folic acid supplement use should be conducted periodically by gynecologists and primary care physicians during annual medical screenings. Mandatory folic acid fortification of staple foods is a complementary approach to overcome limitations of individual behaviors of folic acid supplement intake, and should be considered as it has been proven effective in multiple countries.